CD4+ T cell help in cancer immunology and immunotherapy - Borst, Jannie; Ahrends, Tomasz; Babala, Nikolina; Melief, Cornelis J. M.; Kastenmueller, Wolfgang (Nature reviews. Immunology, 2018)
Cancer immunotherapy aims to promote the activity of cytotoxic T lymphocytes (CTLs) within a tumour, assist the priming of tumour-specific CTLs in lymphoid organs and establish efficient and durable antitumour immunity. During priming, help signals are relayed from CD4+ T cells to CD8+ T cells by specific dendritic cells to optimize the magnitude and quality of the CTL response. In this Review, we highlight the cellular dynamics and membrane receptors that mediate CD4+ T cell help and the molecular mechanisms of the enhanced antitumour activity of CTLs. We outline how deficient CD4+ T cell help reduces the response of CTLs and how maximizing CD4+ T cell help can improve outcomes in cancer immunotherapy strategies.
CRIS-Team Scopus Importer:2023-03-23